PENGGUNAAN MODEL ACTIVE LEARNNG UNTUK MENINGKATKAN PRESTASI BELAJAR DALAM PEMBELAJARAN SEJARAH - Patimah Patimah Patimah (STKIP PGRI TULUNGAGUNG, 2022)
In order to create an effective and innovative historical learning model, an active learning model in learning needs to be developed in order to improve learning achievement. The activeness function in learning is considered important to function the brain optimally, in order to critically analyze text in learning. As writing that uses a qualitative approach to the type of case studies with research sites at SMAN 1 Cidahu. Sources of research data from informants, events, and documents. Data collection techniques by observation, interview and documentation. Data analysis through single case data analysis. Checking the validity of the data through triangulation, research extension, and peer discussion. This paper seeks to explore and analyze in terms of effectiveness, starting from planning active learning models of historical learning, implementing learning with active learning models in history learning, and evaluating learning outcomes. The results showed that the learning model of active learning in history learning is done with the stages of learning planning, learning implementation, and learning evaluation. The results of implementing this active learning model students are able to develop their learning achievement.